Analysis of Mindfulness Practices Using Electroencephalogram (EEG) Interaxon Muse™ Headband Against the Concept of Self-Acceptance of Poststroke Clients - Sulaiman Girivirya (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The Buddhist guidance and counseling model was applied to a client who experienced post-stroke 3 stress disorder and was isolated at the start of the Covid-19 pandemic in 2020. Mindfulness of breathing, body and mind activities is very important in mindfulness practice. Mental relaxation treatments and measurements were administered using the first generation Muse™ "S" Series. Portable and "Muse: Meditation and Sleep" by the InteraXons app, linked by mobile technology (iPad/iOS). This research method uses a single subject research design with a time series approach. However, this report reports qualitatively descriptively about the client's self-acceptance concept after each session of stroke. The research sample was conducted on clients with post-stroke comorbidities. Treatment of mental relaxation sessions using mindfulness techniques. The results of measuring brain wave conditions that are inferred from the Muse™ application show an increase in mental relaxation conditions. Along with that the client's self-acceptance of the illness can be accepted with full awareness by the client. The client underwent a total of twelve guided mental relaxation sessions. In each session, the client feels able to accept the illness, forgive and fully accept himself with love.